Методы и средства курса «Введение в специальность «Физическая и биомедицинская электроника» - Высоцкая, Е. В.; Порван, А. П. (УАДО, 2004)
In this paper the writers offer one of variants of creation by multimedia of electronic educational course « Introduction to a specialty «Physical and biomedical electronics engineering» using modem information technologies in view of teaching’s specificity of discipline. At creation of course were used different multimedia software packages and resources permitting to boost efficiency and to make the process of perception of course more attractive.
Keywords: физическая электроника; биомедицинская электроника